Consequence of Synthetic Bone Substitute Used for Alveolar Cleft Graft Reconstruction (Preliminary Clinical Study) - Al-Rawee, Rawaa Y.; Tawfeeq, Bashar Abdul-Ghani; Hamodat, Ahmed Mothafar; Tawfek, Zaid Salim (Archives of Plastic Surgery, 2023)
Background The outcome of alveolar grafting with synthetic bone substitute (Osteon III) in various bone defect volumes is highlighted.Methods A prospective study was accomplished on 55 patients (6–13 years of age) with unilateral alveolar bone cleft. Osteon III, consisting of hydroxyapatite and tricalcium phosphate, is used to reconstruct the defect. Alveolus defect diameter was calculated before surgery (V1), after 3 months (V2), and finally after 6 months (V3) postsurgery. In the t-test, a significant difference and correlation between V1, V2, and V3 are stated. A p-value of 0.01 is considered a significant difference between parameters.Results The degree of cleft is divided into three categories: small (9 cases), medium (20 patients), and large (26 cases).The bone volume of the clefted site is divided into three steps: volume 1: (mean 18.1091 mm3); step 2: after 3 months, volume 2 resembles the amount of unhealed defect (mean 0.5109 mm3); and the final bone volume assessment is made after 6 months (22.5455 mm3). Both show statistically significant differences in bone volume formation.Conclusion An alloplastic bone substitute can also be used as a graft material because of its unlimited bone retrieval. Osteon III can be used to reconstruct the alveolar cleft smoothly and effectively.
Keywords: alveolus grafting; synthetic bone substitute; secondary bone grafting; alveolar cleft; reconstruction